Lost Circulation Material Berbahan Dasar Rumput Laut (Eucheuma Cottonii ) Sebagai Aditif Dalam Lumpur Pemboran Berbahan Dasar Air Tawar - Nurul Anniza; Purnomosidi; Valentyn B Hattu; Deny I Pellu (Department of Mechanical Engineering, 2026)
This study aims to analyze the effect of adding Eucheuma cottonii seaweed powder as a Lost Circulation Material (LCM) on the characteristics of freshwater-based drilling mud. The variations of seaweed powder concentration used were 0.25 grams, 0.5 grams, 0.75 grams, 1 grams, 1.25 grams 1.5 grams, and 1.75 grams. The parameters analyzed included density, rheological properties (plastic viscosity, yield point, and gel strength), pH, filtration loss, and mud cake characteristics. The results indicate that the addition of Eucheuma cottonii seaweed powder affects the physical, rheological, and chemical properties of the drilling mud. Increasing seaweed concentration tends to increase plastic viscosity, yield point, and gel strength, while density decreases but remains within the API standard limits at certain concentrations. The mud pH remains relatively stable in the range of 8-10. Based on overall performance, the 0.75 g composition provides the most optimal results because it produces the best balance between rheological properties and mud stability compared to other variations. However, the filtration loss obtained at this composition still does not fully meet the API standard. Therefore, Eucheuma cottonii seaweed has potential as a natural LCM, but further development is required to reduce fluid loss in accordance with standard control requirements. Keywords: Eucheuma cottonii, drilling mud, lost circulation material, Rheology.